2002
DOI: 10.1046/j.1365-3032.2002.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Aphid parasitoids detect that an alien plant was present nearby during their development

Abstract: Abstract. Glasshouse and laboratory experiments were conducted with Aphidius rhopalosiphi parasitizing Metopolophium dirhodum to test whether the presence in the same environment of another plant species (tomato or marigold) induced aerial allelopathy in wheat plants.Emerging parasitoids were offered the choice of two odours of wheat plants in an olfactometer ± wheat grown alone and wheat grown in the presence of the second plant species.Female parasitoids responded more strongly than males, but both sexes pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
0
18
1
Order By: Relevance
“…Within 48 h of emergence the females were tested with a choice of two odours in a 2-chamber olfactometer (van Emden et al, 2002) or, in the case of the chilling experiments, a Y-tube olfactometer. Parasitoids which did not respond were omitted from the analysis (details of the analysis are given in the Figure legends).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within 48 h of emergence the females were tested with a choice of two odours in a 2-chamber olfactometer (van Emden et al, 2002) or, in the case of the chilling experiments, a Y-tube olfactometer. Parasitoids which did not respond were omitted from the analysis (details of the analysis are given in the Figure legends).…”
Section: Methodsmentioning
confidence: 99%
“…The cutting out from the mummy of the parasitoid during emergence can be eliminated by excising the parasitoid pupa, so this experiment (van Emden et al, 2002) offered parasitoids emerged from excised pupae a surface contact with mummies from a different plant.…”
Section: Presence Of Other Plant Volatiles In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This conditioned chemosensory responsiveness can influence the host-searching and hostrecognition behaviors of the adult. This effect on host location has already been shown for A. rhopalosiphi (van Emden et al, 2002) but remains to be tested at the host-recognition level. From an applied point of view, the identified chemical stimulus could provide opportunities to manipulate parasitoid behavior in order to enhance oviposition in artificial rearing systems (Battaglia et al, 1995).…”
Section: Discussionmentioning
confidence: 56%
“…Thus, when parasitised aphids were transferred between different plants, the adult parasitoids were attracted to the plant over which they had mummified. Moreover, in a subsequent report, van Emden et al (2002) showed that adult parasitoids responded to odours of an alien plant only if it was present at mummification. The evidence presented herein suggests that exposure of the larvae to the external Conditioning to odours present during mummification disappeared if the pupae of A. rhopalosiphi were excised from the mummies (van Emden et al 1996(van Emden et al , 2002.…”
Section: Discussionmentioning
confidence: 95%